2020
DOI: 10.1111/1759-7714.13716
|View full text |Cite
|
Sign up to set email alerts
|

Combined small cell lung carcinoma harboring ALK rearrangement: A case report and literature review

Abstract: Combined small cell lung cancer (c-SCLC) is a relatively rare subtype of SCLC and is defined by the combination of SCLC and any elements of non-small cell carcinoma (NSCLC). Standard chemotherapy for patients with c-SCLC has not yet been established. Gene mutations such as epidermal growth factor receptor (EGFR) mutations may be detected in patients with c-SCLC. However, little is known about anaplastic lymphoma kinase (ALK) rearrangement in c-SCLC patients. Here, we report a young female patient who was succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…However, clinical studies of immunotherapy combined with chemotherapy in extensive-stage C-SCLC are very limited, with only a small number of individual case reports. Niitsu et al [ 13 ] reported a case of epidermal growth factor receptor mutation-positive C-SCLC that developed intrinsic resistance to the tyrosine kinase inhibitor oximotinib; this patient subsequently received 6 cycles of dose-adjusted durvalumab in combination with etoposide and carboplatin, which showed a sustained treatment response and disease control. Dong et al [ 7 ] reported a case of C-SCLC containing three different histological components; the solid tumor masses were significantly reduced after 2 cycles of treatment with camrelizumab combined with paclitaxel and cisplatin and met the RECIST criteria for partial response, suggesting that immunochemotherapy may be a feasible regimen for the treatment of extensive-stage C-SCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical studies of immunotherapy combined with chemotherapy in extensive-stage C-SCLC are very limited, with only a small number of individual case reports. Niitsu et al [ 13 ] reported a case of epidermal growth factor receptor mutation-positive C-SCLC that developed intrinsic resistance to the tyrosine kinase inhibitor oximotinib; this patient subsequently received 6 cycles of dose-adjusted durvalumab in combination with etoposide and carboplatin, which showed a sustained treatment response and disease control. Dong et al [ 7 ] reported a case of C-SCLC containing three different histological components; the solid tumor masses were significantly reduced after 2 cycles of treatment with camrelizumab combined with paclitaxel and cisplatin and met the RECIST criteria for partial response, suggesting that immunochemotherapy may be a feasible regimen for the treatment of extensive-stage C-SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…However, targeted therapy can also be tried in patients who have failed immunochemotherapy. Niitsu et al [ 13 ] reported a young female patient who was successfully treated with alectinib for ALK-positive C-SCLC after failure of immunochemotherapy for SCLC and cytotoxic chemotherapy for adenocarcinoma. Radiotherapy is rarely used in the treatment of C-SCLC and is often combined with other regimens.…”
Section: Discussionmentioning
confidence: 99%
“…There are also detected in C-SCLCs, which usually contain the adenocarcinoma component. 20 However, RET fusions have not been reported in C-SCLC. Herein, we present a patient with stage IV C-SCLC harboring the KIF5B-RET fusion.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the likelihood of EGFR mutation in C-SCLC varies from 15% to 20% ( 8 ). Per some case studies, EGFR or ALK tyrosine kinase inhibitors may be effective ( 9 ). The patient was only tested for an EGFR mutation because of financial and healthcare concerns in this case; the results were negative for the EGFR gene.…”
Section: Discussionmentioning
confidence: 99%